2015
DOI: 10.1111/jsr.12329
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, health and memory: comparing parents of typically developing children and parents of children with special health‐care needs

Abstract: SUMMARYParents of children with special healthcare needs (CSHCNs) report poorer sleep than parents of typically developing (TD) children, which has been associated with poorer mental health. The relations between sleep disturbances and general health and memory among this population are unknown. The current study aimed to replicate the findings that parents of CSHCNs report poorer sleep quality than parents of TD children, and further examine how sleep is related to general health and memory. Participants (75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…Stronger EF capacity was linked with less negative parenting as found in prior research, but only at moderate to long sleep durations-in contrast, there was no association with parenting when sleep durations were short (i.e., poor sleep). Although there are some studies on children with illnesses showing that mothers of young children report shorter amounts of total sleep (McBean & Schlosnagle, 2016;McCann, Bull, & Winzenberg, 2015), there is no literature on the intersection of sleep duration and parenting behaviors that we could use to interpret this "overriding" interactive effect. However, it is clear from the broader sleep literature that shorter sleep duration is indicative of not only poorer quality sleep but also of acute and chronic stress, as well as poorer sleep hygiene in youth and adults (Brown, Buboltz, & Soper, 2002;Olds, Maher, & Matricciani, 2011;Otsuka et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Stronger EF capacity was linked with less negative parenting as found in prior research, but only at moderate to long sleep durations-in contrast, there was no association with parenting when sleep durations were short (i.e., poor sleep). Although there are some studies on children with illnesses showing that mothers of young children report shorter amounts of total sleep (McBean & Schlosnagle, 2016;McCann, Bull, & Winzenberg, 2015), there is no literature on the intersection of sleep duration and parenting behaviors that we could use to interpret this "overriding" interactive effect. However, it is clear from the broader sleep literature that shorter sleep duration is indicative of not only poorer quality sleep but also of acute and chronic stress, as well as poorer sleep hygiene in youth and adults (Brown, Buboltz, & Soper, 2002;Olds, Maher, & Matricciani, 2011;Otsuka et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies concluded that ASD caregivers (both men and women) had poorer declarative verbal memory, but they outperformed non-caregivers in inhibitory control and visuospatial skills (Romero-Martínez, Ruiz-Robledillo, et al, 2016;Romero-Martínez & Moya-Albiol, 2015). Moreover, this type of caregiver was found to have more retrospective and prospective memory failures (assessed by a questionnaire) in a diary over the course of a week than non-caregivers (Lovell, Elliot, Liu, & Wetherell, 2014;Mcbean & Schlosnagle, 2016). However, there is a gap in the scientific literature analysing whether cognitive-behavioural interventions, to reduce health complaints and stress levels, could be effective in offsetting normal age-related cognitive decline or even improving certain aspects of cognition in this population.…”
Section: Introductionmentioning
confidence: 95%
“…The majority of research in caregivers has been conducted in populations in which the care recipient has dementia and/or Alzheimers' disease, few studies having analysed cognition in caregivers of offspring with autism spectrum disorder (ASD). A number of studies have identified poor performance in processing speed, selective attention, working memory for digits, words and visuospatial information, learning words and long-term memory for words in caregivers of people with dementia, Alzheimers' disease, stroke survivors, terminally ill family members, individuals with osteoporotic fractures and/or eating disorders compared to control participants (Caswell et al, 2003;Chen & Botticello, 2013;Corrêa et al, 2015;de Vugt et al, 2006;Mackenzie et al, 2007;Mcbean & Schlosnagle, 2016;Romero-Martínez, Ruiz-Robledillo, Moya-Albiol, 2016;Vitaliano, Ustundag, & Borson, 2016). Moreover, longitudinal studies have indicated that chronic stress in caregivers of people with dementia and/or Alzheimers' disease tends to accelerate age-related cognitive decline in several cognitive domains, including general cognitive status and processing speed (Dassel, Carr, & Vitaliano, 2015;Vitaliano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep quality due to sleep deprivation is a frequent problem for parents of children with special healthcare needs (McBean & Schlosnagle, ; Mörelius & Hemmingsson, ), leading to forgetfulness, lack of energy, impatience with the family and negative mood (Angelhoff, Edéll‐Gustafsson, & Mörelius, ; McCann, Bull, & Winzenberg, ). Mood is a subjective description of a persons’ emotional state, determined by disposition and circumstances.…”
Section: Introductionmentioning
confidence: 99%